Characterization of rectus femoris lesions in knee osteoarthritis at different stages and the effect of ultrasound-guided acupotomy - Yu, Wen-Ying; Liu, Jing; Lin, Ze-Hao; Liu, Hong; Zhang, Liang-Zhi; Feng, Xiang-Long; Xiu, Zhong-Biao (Frontiers in Physiology, 2025)
IntroductionChronic injury to the rectus femoris muscle induces and exacerbates the progression of knee osteoarthritis (KOA). However, the lesion characteristics of the rectus femoris muscle in KOA at different stages have not been fully characterized. The aim of this study was to analyze the pattern of lesion characteristics of the rectus femoris muscle at different stages of KOA and to investigate the mechanism by which ultrasound-guided acupotomy operations can prevent and control KOA.MethodsEarly, middle, and late-stage rabbit KOA models were constructed using the modified Videman method. Ultrasonography was used to record the elastic modulus and cross-sectional area of the rectus femoris muscle, and morphology was used to observe the ultramicroscopic changes in the rectus femoris muscle and assess the degree of fibrosis. Additionally, ultrasound-guided acupotomy operations were performed on the rabbit model of late-stage KOA, and alterations in the key molecular markers of rectus femoris fibrosis were determined using Western Blot and qPCR methods.ResultsAs the disease progressed, the elastic modulus of the rectus femoris muscle in KOA rabbits gradually increased, the cross-sectional area gradually decreased, and the degree of fibrosis increased. In contrast, the degree of fibrosis in the rectus femoris muscle improved after ultrasound-guided acupotomy intervention.ConclusionThese findings highlight the gradual increase in the modulus of elasticity, the gradual decrease in cross-sectional area, and the increased fibrosis of the rectus femoris muscle in KOA rabbits as the disease progressed. Ultrasoundguided acupotomy operations have been shown to have a protective effect on KOA cartilage and to delay the progression of KOA by ameliorating pathological changes in the rectus femoris muscle. The mechanism may involve reducing chronic injury to the rectus femoris muscle and protecting joint homeostasis by attenuating the degree of rectus femoris fibrosis.